Evaluating the influence of deformation variables on dynamic recrystallization behavior using a crystal plasticity model. (1st June 2023) - Chatterjee, Ritam; Narayana Murty, S V S; Alankar, Alankar
Abstract: The present study is an attempt to model dynamic recrystallization (DRX) in a single phase metal using a mean field crystal plasticity (MFCP) based approach. A new empirical equation is proposed to model nucleation, in which the nucleation rate is a function of microstructure and plasticity descriptors that are known to affect DRX behavior, such as the temperature, strain rate, grain fineness and stored energy. Grains undergo nucleation when their dislocation density exceeds a threshold value. Subsequently, new grains grow based on the difference in stored deformation energy with respect to the average value over all grains. The MFCP-DRX model is able to correctly predict trends for the flow stress, dislocation density evolution, grain size evolution and kinetics across a range of temperatures and strain rates for uniaxial compression. Transition of the flow stress from single to multiple peaks is observed with increasing temperature and decreasing strain rate, thus comparing well against known DRX trends. The evolutions of crystallographic texture during DRX in uniaxial compression and plane strain compression are compared against experimental observations. A sensitivity analysis is conducted to understand the effect of variables on nucleation and growth. The competition between nucleation and growth dominated deformation in different strain regimes is analyzed in detail across various temperatures and strain rates.